MEFV mutations are increased in Behçet's disease (BD) and are associated with vascular involvement - (:unkn) unknown (My University, 2003)
OBJECTIVE: A high prevalence of Behçet's disease (BD) among familial Mediterranean fever (FMF) patients has been described recently and a weak association of BD and certain MEFV gene mutations, originally linked to FMF, has been reported in an ethnically mixed population from France. We further investigated the presence of MEFV mutations in BD patients from Turkey, a country with a high prevalence of both disorders. METHODS: The frequencies of three FMF-related MEFV mutations (M694V, M680I and V726A) were investigated in BD patients (n = 57) by molecular genetic studies using a polymerase chain reaction with the ARMS method. All patients fulfilled the International Study Group Criteria for the diagnosis of BD and patients with FMF-like symptoms or a chronic inflammatory disease were excluded. RESULTS: Fifteen BD patients were found to carry one single MEFV mutation (26%), compared to 9.1% in the control group (p = 0.003, OR: 3.5, 95% CI: 1.6-7.6). Among 20 BD patients with vascular involvement, 11 (55%) had MEFV mutations compared to 4 patients (11%) in the non-vascular group (p = 0.001, OR: 10, 95% CI: 2.5-39.3). M694V was the dominant mutation in our study group (11 out of 15 patients with mutated alleles). Six out of 7 female patients with vascular involvement carried MEFV mutations in contrast to 5 out of 13 male patients (85.7% versus 38.4%, p = 0.07, OR: 0.1, 95% CI: 0.009-1.14). No association with other clinical manifestations was observed. CONCLUSION: MEFV mutations, originally linked to FMF, may act as a genetic susceptibility factor for other inflammatory disorders such as vascular BD.
Keywords: Adult; Female; Humans; Middle Aged; Behcet Syndrome; Turkey; Prevalence; Male; Age Distribution; Sex Distribution; Comorbidity; Cohort Studies; Gene Frequency; Genetic Predisposition to Disease; Mutation; Alleles; Prospective Studies; Probability; Familial Mediterranean Fever; Vascular Diseases; DNA Mutational Analysis